Analisis Efektivitas Layanan Dalam Penelusuran Informasi di Perpustakaan UINSU - Iyen Supit; Anggraini Simatupang; Fauziyah Siregar; Rahot Martua R Rambe; Franindya Purwaningtyas (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
A good library service is one that can meet the needs, tastes, interests and desires of users. So, through library services, users can obtain the information they need optimally and take advantage of the various search tools available. This research uses a type of qualitative research that requires as much information and data as possible to achieve the research objectives. This type of research is a case study because this research is carried out in depth with an institution and with a narrow subject. As a case study, the data collected comes from various sources of literature. This research resulted in that in the UINSU library itself, library service activities in tracing student information were quite good, starting from the service of time, place, and other excellent services that were included in the best service category. Keywords: Information Retrieval, Information Services, Libraries